2016
DOI: 10.3390/biom6040043
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Binge Alcohol Administration Dysregulates Hippocampal Genes Involved in Immunity and Neurogenesis in Simian Immunodeficiency Virus-Infected Macaques

Abstract: Alcohol use disorders (AUD) exacerbate neurocognitive dysfunction in Human Immunodeficiency Virus (HIV+) patients. We have shown that chronic binge alcohol (CBA) administration (13–14 g EtOH/kg/wk) prior to and during simian immunodeficiency virus (SIV) infection in rhesus macaques unmasks learning deficits in operant learning and memory tasks. The underlying mechanisms of neurocognitive alterations due to alcohol and SIV are not known. This exploratory study examined the CBA-induced differential expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…phosphorylation domains are present in the full-length TrkB (TrkB-FL) receptor, which is expressed primarily on neurons in vivo (Frisen et al, 1993) and this phosphorylation site was selected for its specific activation of AKT and ERK 44/42, critical mediators of BDNF/TrkB-mediated neuronal growth and survival (Minichiello, 2009). These outcomes were considered of primary interest based on previous findings in which expression of genes related to neuronal growth and survival were dysregulated in CBA/SIV+ macaques compared to SUC/SIV+ macaques (Maxi et al, 2016). Consistent with the reduced phosphorylation at TrkB Y515, reduced phosphorylation of the signaling enzyme AKT was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phosphorylation domains are present in the full-length TrkB (TrkB-FL) receptor, which is expressed primarily on neurons in vivo (Frisen et al, 1993) and this phosphorylation site was selected for its specific activation of AKT and ERK 44/42, critical mediators of BDNF/TrkB-mediated neuronal growth and survival (Minichiello, 2009). These outcomes were considered of primary interest based on previous findings in which expression of genes related to neuronal growth and survival were dysregulated in CBA/SIV+ macaques compared to SUC/SIV+ macaques (Maxi et al, 2016). Consistent with the reduced phosphorylation at TrkB Y515, reduced phosphorylation of the signaling enzyme AKT was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our group have shown that chronic binge alcohol (CBA) administration unmasks cognitive impairment in simian immunodeficiency virus (SIV)-infected macaques (Winsauer et al, 2002). Subsequent microarray analysis of hippocampus (HP) demonstrated increased expression of genes involved in immune function and dysregulated gene expression involved in neurogenesis (Maxi et al, 2016), which may result from impaired brain-derived neurotropic factor (BDNF) signaling. Both alcohol and HIV can suppress neurotrophic factors critical for neuronal growth and survival (Bachis et al, 2012;Boyadjieva and Sarkar, 2013;Fields et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously showed chronic binge alcohol (CBA) administration unmasks neurocognitive deficits in simian immunodeficiency virus (SIV)-infected, ARTnaive macaques [31]. Subsequent studies, in agreement with others [21][22][23], identified disruptions in growth factor expression and signaling as potential mechanisms contributing to cognitive impairment [20]. Brain-derived neurotrophic factor (BDNF) is a neuroprotective factor regulating synaptic plasticity and cognitive function.…”
Section: Introductionmentioning
confidence: 75%
“…In a murine model of HIVE, neuropathology persists despite suppressed neuroinflammation and central nervous system (CNS) viral replication [19]. Previous work from our group and others suggest disruptions in growth factor expression and signaling likely contribute to HIV neuropathology and cognitive impairments [20][21][22][23][24]. Whether ART can protect against neuroinflammation and improve growth factor signaling remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…In a murine model of HIVE, neuropathology persists despite suppressed neuroinflammation and CNS viral replication. Preclinical studies suggest that disruptions in growth factor expression and signaling likely contributes to HIV neuropathology and cognitive impairments ( Maxi et al, 2016 ). Chronic binge alcohol unmasks neurocognitive deficits in SIV-infected, non-ART treated macaques ( Winsauer et al, 2002 ).…”
Section: Mechanisms Implicated In Alcohol-human Immunodeficiency Virus Interactions Increasing Risk and Pathogenesis Of Cardiometabolic Smentioning
confidence: 99%